2013
DOI: 10.1111/ahe.12059
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Foamy Epithelial Surface Cells in the Canine Endometrium

Abstract: In mature bitches, endometrial epithelial surface cells modify function and corresponding morphology during the oestrous cycle. During late metoestrous, endometrial epithelial surface cells frequently accumulate fat and thereby adopt a foamy morphology. This cyclic appearance of foamy endometrial epithelial cells (fEECs) seems to be physiological in the dog, whereas in other species, it indicates pathological changes. Function of these fEECs has not been identified until now. Therefore, the aim of the study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The anestrus phase of the estrus cycle was characterized by hardly notable crypts of the epithelium. All described changes were described by other authors [2][3][4]16,17]. Also, beside the histological changes on the endometrium, different phases of the estrus cycle were also characterized by cyclic changes of estrogen and progesterone receptor concentrations on the uterine cells which was confi rmed by using an immunohistochemical technique.…”
Section: Discussionmentioning
confidence: 74%
“…The anestrus phase of the estrus cycle was characterized by hardly notable crypts of the epithelium. All described changes were described by other authors [2][3][4]16,17]. Also, beside the histological changes on the endometrium, different phases of the estrus cycle were also characterized by cyclic changes of estrogen and progesterone receptor concentrations on the uterine cells which was confi rmed by using an immunohistochemical technique.…”
Section: Discussionmentioning
confidence: 74%
“…Protein signals for LepR and Lep in the uteri of women were predominantly localized in the luminal epithelium, in the endometrial glands and in stromal cells [ 3 ], which is in accordance with our study. Bartel et al [ 50 ] also described immunoreactivity for both proteins in the surface and glandular epithelium, and occasional Lep staining in the stromal parts of the endometrium during diestrus and anestrus in non-pregnant dogs, but the date of ovulation was not known. In contrast to our study, Schäfer-Somi et al [ 37 ] and Beceriklisoy et al [ 39 ] did not detect Lep mRNA expression by qualitative PCR in the uterus of non-pregnant bitches in early diestrus or in pregnant dogs at pre-implantation and at d 20–35 of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, Lep expression in the canine uterus was only examined in the first half of gestation using qualitative PCR, which yielded negative results [ 37 , 39 ]. Bartel et al [ 50 ] found Lep and LepR immunoreactivity in the uteri of non-pregnant bitches, but pregnant dogs were not studied.…”
Section: Introductionmentioning
confidence: 99%
“…During the estrous cycle, the endometrium of the bitch undergoes distinct morphological and biochemical changes [9,[12][13][14][15]. The important role in regulating these changes is mainly attributed to steroidal hormones [10,15].…”
Section: Discussionmentioning
confidence: 99%